Teachers’ Perception towards STEM and VMC in SoSEs of Delhi An Exploratory Study - Singh, Sunita; Chaurasiya, Deepika Pradeep; Pal, Rashmi (INDIAN EDUCATIONAL REVIEW, 2025)
The Government of Delhi established Schools of Specialised Excellence (SoSEs) in 2021 to serve students with an interest and aptitude in specialised domains. These institutions offer a variety of disciplines, like Science, Technology, Engineering and Mathematics (STEM) education, humanities, 21st century skills, armed forces, performing and visual arts from Grades 9 to 12. This study aimed to explore teachers’ perception towards STEM and Vidya Mandir Classes (VMC) initiatives in SoSEs and identified the facilities and support services available in SoSEs, including challenges faced and adopted coping strategies of teachers. Questionnaires, semi-structured interviews, observation and focus group discussions were used to analyse data qualitatively. Further findings were analysed in categories like teachers’ perception towards access to STEM education and improvisation of VMC at SoSEs, teachers’ points of view towards the aim and nature of VMC versus mainstream education, challenges faced by regular teachers of SoSEs in connection with VMC classes. Most SoSE teachers viewed STEM education and VMC as a positive initiative to assist parents who could not afford the high costs of private coaching so that their children could pass competitive exams, such as IIT JEE, NEET, etc. Additionally, SoSE teachers also faced challenges like managing timetables, negotiating between NCERT textbooks and competitive reading material of VMC, and their own identity and responsibility. The study suggests recruiting or hiring teachers with an advanced understanding of STEM-related content and pedagogy. It also indicates a requirement to conduct VMC classes offline, beyond the school boundary so that learners can derive maximum benefit and balance with mainstream regular courses.